2021
DOI: 10.1371/journal.pone.0246399
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and clinical prediction formula for the evaluation of obstructive sleep apnea in Asian adults

Abstract: Obstructive sleep apnea is a highly prevalent cyclic repetitive hypoxia-normoxia respiratory sleep disorder characterized by intermittent upper-airway collapse. It is mainly diagnosed using in-laboratory polysomnography. However, the time-spatial constraints of this procedure limit its application. To overcome these limitations, there have been studies aiming to develop clinical prediction formulas for screening of obstructive sleep apnea using the risk factors for this disorder. However, the applicability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
3
14
1
Order By: Relevance
“…The most recent study by Park et al [ 66 ], performed in 2021 with a validation data set of 916 participants (largest sample), only reached values of 78% and 76% for sensitivity and specificity, respectively, when compared with the 2 previous best models. This was also a logistic regression, electing BMI, age, sex, Berlin questionnaire score, and tonsil grade as the clinical factors for an OSA definition of AHI≥5.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent study by Park et al [ 66 ], performed in 2021 with a validation data set of 916 participants (largest sample), only reached values of 78% and 76% for sensitivity and specificity, respectively, when compared with the 2 previous best models. This was also a logistic regression, electing BMI, age, sex, Berlin questionnaire score, and tonsil grade as the clinical factors for an OSA definition of AHI≥5.…”
Section: Discussionmentioning
confidence: 99%
“…OSA has been associated with numerous negative outcomes, including sleep disruption, daytime sleepiness, cognitive dysfunction, and cardiovascular disease [1]. There has been increasing concern regarding lapses in attention due to EDS, a major OSA symptom, leading to increased risk of traffic accidents and errors by workers that can cause serious industrial accidents [2][3][4]. Generally, OSA is diagnosed based on the apnea-hypopnea index (AHI), which indicates the number of apnea/hypopnea events per hour of sleep, wherein a pause in breathing lasting 10 s or longer with an associated decrease in blood oxygenation is considered an event.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we showed that BCF significantly improved depending on the degree of OSA in type 2 diabetes patients with moderate/severe IMS. There are some influencing factors of inducing and progressing OSA, such as micrognathia, nasal septum deviation, tonsil swelling, adenoid hypertrophy and severe obesity [18][19][20][21] . Among them, severe obesity is known to be the most influential factor of OSA, because respiratory mechanical impairment leads to upper airway collapse during sleep 22 .…”
Section: Discussionmentioning
confidence: 99%